KEARIFAN LOKAL & HAK AZAZI MANUSIA PERSPEKTIF ABDULLAHI AHMED AN-NA’IM - Musleh, Musleh; Wardi, Moh.; Jamiluddin, Jamiluddin (Reflektika, 2019)
Human rights are closely related to local culture. In the sense that human rights standards to be accepted and implemented require local cultural legitimacy. People are more willing to follow these human rights standards when they accept the norms and values that underlie these standards as legitimate and valid from the point of view of their own culture. In other words, the stronger the legitimacy of human rights standards, the more they will be voluntarily followed by the people in general and the better their implementation by official state organs. Conversely, according to them, the weaker the legitimacy of human rights standards, the more frequently they will be violated by the population and the more impossible it will be enforced by the state. So this article wants to examine more deeply the opinion of Abdullahi Ahmed An-Na'im